Electrochemical property of nanosphere-like MgO electrode synthesized via SILAR in asymmetric supercapacitor - Gaikwad, D. S.; Bobade, R. G.; Suryawanshi, V. B.; Nakate, U. T.; Shaikh, S. F.; Al-Enizi, Abdullah M.; Dabke, N. B.; Lokhande, B. J.; Ambare, Revanappa C. (Journal of Materials Science-Materials in Electronics, 2024)
In this research article, we synthesized nanospheres of MgO thin-film substrate using the successive ionic layer adsorption and reaction (SILAR) technique on stainless steel substrates. The final optimized sample was used for physical characterization. XRD revealed the cubic structure of the MgO electrode. Additionally, it was utilized for electrochemical supercapacitive characterization, including cyclic voltammetry (CV), chronopotentiometry, and electrochemical impedance spectroscopy (EIS). Results showed that MgO nanospheres exhibited a higher specific capacitance (SC) of 536.06 F/g. The maximum values of specific energy and specific power were 30.79 Wh/kg and 1420 W/kg, respectively, at 2 mA/cm2 in 1-M KOH. The EIS plot confirmed an internal resistance (Ri) of 0.86 omega, indicating good power performance and outstanding rate capability of MgO nanospheres. This material demonstrated excellent cycling capability, retaining 91.38% capacitance after 5000 CV cycles. The MgO//AC device displayed an SC of 210.21 F/g at 5 mV/s in a PVA-KOH solid-state electrolyte. With an energy density of 23.90 Wh/kg and a power density of 1.84 kW/kg, the asymmetric supercapacitor performance showed that the MgO-based electrode is suitable for use in actual device manufacturing. After 5000 CV cycles, the supercapacitor device exhibited exceptional capacitance retention of 92.93%. Thus, this research successfully demonstrated the usefulness of the simple and affordable SILAR method for synthesizing pure MgO nanostructures for application in supercapacitors.